If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -8 = 10 + 2x Reorder the terms: -8 + 4x = 10 + 2x Solving -8 + 4x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + 4x + -2x = 10 + 2x + -2x Combine like terms: 4x + -2x = 2x -8 + 2x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + 2x = 10 + 0 -8 + 2x = 10 Add '8' to each side of the equation. -8 + 8 + 2x = 10 + 8 Combine like terms: -8 + 8 = 0 0 + 2x = 10 + 8 2x = 10 + 8 Combine like terms: 10 + 8 = 18 2x = 18 Divide each side by '2'. x = 9 Simplifying x = 9
| .12y+0.05(y+5000)=1440 | | 4(x-3)=3(x-2) | | 8r-28=-8+3r | | y-(-1)=(-2/5)(x-5) | | -4x-y=-1 | | 6g+2(-7+4g)=1-g | | -8-7/5 | | 6.5x-13.4=1.3-6.7x | | -8-10/5 | | y-(-1)=(2/5)(x-5) | | -2x-2(-2x-18)=48 | | -4x-3x-2=-3x-4 | | 2(x+38)+13x+10=90 | | 8.2x-2.3x=177 | | 4ln(x)-ln(x^4)=0 | | -8x-11x=152 | | 1/2(10x-16)=40 | | 74h=257-6h | | 65+x=a(50+x+75) | | w-3d=6 | | a=(3C+4C) | | 8n+4n=8(2n+6)-4(2+2n) | | g(x)-6x^2-7xg(3)= | | (2.5)-(-0.5)=3 | | g(x)-6x^2-7x= | | 4p+1/4=16 | | 6/7p-5/7p-17=18 | | x^3+3x^2-7x=21 | | 2x-6(5x-15)=-190 | | 26h=234 | | 9n+2n-3n+2=3n+2n+n | | -3y=0.5-2-5 |